Surveillance of COVID-19 in Cameroon: Implications for policymakers and the healthcare system - Bruno Bonnechère; Osman Sankoh; Sékou Samadoulougou; Jean Cyr Yombi; Fati Kirakoya-Samadoulougou (AOSIS, 2021)
At first less impacted than the rest of the world, African countries, including Cameroon, are also facing the spread of COVID-19. This study aimed to analyze the spread of the COVID-19 in Cameroon, one of the most affected countries in sub- Saharan Africa. We used the data from the Africa Centre for Disease Control and Prevention, reporting the number of confirmed cases and deaths, and analyzed the regularity of tests and confirmed cases and compared those numbers with neighboring countries. We tested different phenomenological models to model the early phase of the outbreak. Since the first reported cases on the 7th of March, 18,662 people have been diagnosed with COVID-19 as of the 24th of August, 186,243 tests have been performed, and 408 deaths have been recorded. New cases have been recorded only in 50% of the days since the first reported cases. There are considerable disparities in the reporting of daily cases, making it difficult to interpret these numbers and to model the evolution of the pandemic with the phenomenological models. Currently, following the finding from this study, it is challenging to predict the evolution of the pandemic and to make comparisons between countries as screening measures are so sparse. Monitoring should be performed regularly to provide a more accurate estimate of the situation and allocate healthcare resources more efficiently.